Intrauterine adhesion - Peng-Hui Wang; Szu-Ting Yang; Wen-Hsun Chang; Chia-Hao Liu; Hung-Hsien Liu; Wen-Ling Lee (Elsevier, 2024)
Intrauterine adhesions (IUA) occurred in the reproductive-age women are a big economic and health problem, resulting in severe impairment of social, psychological and physical function of the female genital organs. IUA-related symptoms or signs are varied greatly from free of symptoms or ambiguous symptoms (an incidental finding during the intervention) to ceased menstruation and loss of fecundability. The underlying pathophysiology is not completely understood, but intrauterine damage with broken basal layers of the endometrium formatting scar tissues or fibrosis in the endometrium with subsequently causing partial or complete occlusion of the uterine cavity may be a well-accepted hypothesis. Previously, infection is the most common cause to develop IUA, but now, intrauterine surgery may be a critical cause contributing to the majority of cases of IUA. In the current review, update information about the etiology, epidemiology, pathophysiology, sequelae and prevention of IUA will be renewed. We emphasize the importance of awareness of IUA, and primary prevention should be considered in the routine clinical practice if intrauterine surgery has been applied, based on uncertainty of ideal treatment for the established IUA and unpredictable outcomes after IUA treatment. So far, evidence supports that hyaluronic acid with/without other strategy is the most valuable and effective method to reduce the formation and re-formation of IUA as well as to achieve the best fertility outcome.